Antifungal activity of some medicinal plants against Fusarium oxysporum f.sp. Iycopersici - and HEERAL LAL YADAV, DEEPAK KUMAR SRIVASTAVA* (Indian Phytopathology, 2008)
The antifungal activity of ethanolic extracts of medicinal plants were evaluated against Fusarium oxysporum f.sp. Iycopersici involved in wilt disease of tomato. On screening the ethanolic extracts of different plant parts of 45 medicinal plants for their antifungal activity by "modified paper disc technique". The ethanolic extract of flower of Desmostachya bipinnata L. exhibited maximum toxicity against the test fungus inhibiting the mycelial growth upto 96%.